2016
DOI: 10.1021/acs.chemmater.6b01257
|View full text |Cite
|
Sign up to set email alerts
|

Increased Optoelectronic Quality and Uniformity of Hydrogenated p-InP Thin Films

Abstract: ABSTRACT:The thin-film vapor-liquid-solid (TF-VLS) growth technique presents a promising route for high quality, scalable and cost-effective InP thin films for optoelectronic devices. Towards this goal, careful optimization of material properties and device performance is of utmost interest. Here, we show that exposure of polycrystalline Zn-doped TF-VLS InP to a hydrogen plasma (in the following referred to as hydrogenation) results in improved optoelectronic quality as well as lateral optoelectronic uniformit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Electrically active intrinsic point defects, which lead to unintentional mid‐gap defect states including interstitials and vacancies with shallow energy levels, are detrimental to the optoelectronic device performance. [ 20 ] Therefore, investigations on 2D MHPs with low defect density were reported. PDs based on (PEA) 2 PbI 4 ·(CH 3 NH 3 PbI 3 ) n −1 with low defect density can achieve high D * of 10 13 Jones due to lower defect levels compared with 3D perovskites.…”
Section: Low‐dimensional Mhp Pdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrically active intrinsic point defects, which lead to unintentional mid‐gap defect states including interstitials and vacancies with shallow energy levels, are detrimental to the optoelectronic device performance. [ 20 ] Therefore, investigations on 2D MHPs with low defect density were reported. PDs based on (PEA) 2 PbI 4 ·(CH 3 NH 3 PbI 3 ) n −1 with low defect density can achieve high D * of 10 13 Jones due to lower defect levels compared with 3D perovskites.…”
Section: Low‐dimensional Mhp Pdsmentioning
confidence: 99%
“…Electrically active ions or other impurities might segregate along grain boundaries, causing nonuniform electrical properties over the films. [ 20 ] Moreover, it is revealed that the grain boundaries in polycrystalline MHPs are especially unstable and highly vulnerable to moisture. [ 21 ] These effects hinder their practical applications in stable functional devices.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 For CH 3 residing deep in the gap are rarely observed. In this regard, highly sensitive sub-bandgap EQE is a particularly powerful approach because it is capable of probing ultra-low photocurrents due to sub-bandgap absorption that can be several orders of magnitude weaker than absorption at E g .…”
mentioning
confidence: 99%
“…Work is currently underway on the use of a halide transport agent to overcome these hurdles. Similar difficulties controlling dopant distribution are likely in TF-VLS growth as dopants percolate to grain edges (where diffusion rates are typically much higher) in the final device …”
mentioning
confidence: 91%
“…This provided final N A = 1.9 × 10 17 cm –3 and enabled InP photocathodes for PEC water splitting . Later work showed that treatment of the film postdoping with hydrogen plasma increased the optoelectronic quality and uniformity of the doped material by forming neutral complexes with Zn …”
mentioning
confidence: 98%